Effect of Incubation Duration of Incorporated Organics on Saturated Hydraulic Conductivity, Aggregate Stability and Sorptivity of Alluvial and Red-Laterite Soils - Prasanta Kumar Bandyopadhyay, Arindam Sarkar and (Journal of the Indian Society of Soil Science, 2019)
Improvement in soil hydro-physical properties is a pre-requisite for maintaining soil quality and sustaining agricultural productivity. The objective of this study was to see the effect of degree of decomposition of farmyard manure (FYM) and vermicompost on aggregation indices viz., water stable aggregate (WSA), mean weight diameter (MWD) and aggregate stability (AS), and water transmission properties namely, saturated hydraulic conductivity (Ks) and sorptivity (S) of two contrasting soils (red-laterite and alluvial soils). Soils were incubated with FYM and vermicompost @ 20 t ha-1 for 60 days at field capacity moisture content under laboratory condition and analyzed at 0, 20, 40 and 60 days of incubation (DOI) for hydro-physical and soil organic carbon (SOC) content. Results indicated that the influence of organics was more predominant in red-laterite soil having more iron and aluminium oxides and lower clay content than alluvial soil. Upon incubation, the organic treated red-laterite and alluvial soils increased 73 and 15 per cent SOC, 16 and 13 per cent micro-porosity, 119 and 412 per cent Ks, 25 and 19 per cent WSA, 45 and 11 per cent MWD and 31 and 26 per cent S, respectively. Similarly, vermicompost and FYM treated soils increased 44 and 43 per cent SOC, 17 and 11 per cent micro-porosity, 622 and 239 per cent Ks, 31 and 13 per cent WSA, 33 and 24 per cent MWD and 46 and 11 per cent S. Bulk density (BD) varied from 1.54 to 1.38 and 1.31 to 1.24 Mg m-3, respectively for red-laterite and alluvial soils during the entire incubation period with a strong negative relationship (r = -0.97, p< 0.001) with micro-porosity. Strong positive correlations between WSA and SOC (r = 0.58, p < 0.01), MWD and SOC (r = 0.74, p < 0.001) and AS and SOC (r = 0.73, p < 0.001) were observed indicating that the AS would increase 3.8 per cent with the increase in SOC by 1% in both soils. Sorptivity was positively and significantly related to SOC (r = 0.55, p<0.01) and micro-porosity (r = 0.51, p<0.01), however, had a negative relationship with BD (r = -0.51, p<0.01). Vermicompost had shown better results in structural as well as hydro-physical properties as compared with FYM in both soils.